Optimization of sterlet (Acipenser ruthenus) egg incubation - Cheng, Yu; Xin, Miaomiao; Gela, David; Rodina, Marek; Tučková, Vladimíra; Kašpar, Vojtěch; Siddique, Mohammad Abdul Momin; Shelton, William L; Linhart, Otomar (Animal reproduction science, 2020)
Sterlet Acipenser ruthenus was used to assess egg and embryo development when incubated at 17 °C in Petri dishes placed in a hatchery tank (300 L recirculating dechlorinated water) with incubation occurring in a static tabletop system in an air-conditioned laboratory, or in a 700 L Q-cell incubator. Eggs in each dish were placed in a plastic box with 300 mL dechlorinated water. Separated eggs from three individual females were fertilized using pooled sperm from four males with there being four replicates. There were no differences (P > 0.05) in mean percentages of neurulation and embryos undergoing cleavage for eggs incubated in the hatchery tank and with use of the static tabletop system. Furthermore, there were no differences (P > 0.05) in percentage of embryos undergoing cleavage, neurulation and hatching for each female when eggs were incubated using the two systems. Results indicate a Petri dish placed in a small plastic box with 300 mL of dechlorinated water was adequate for incubation of sterlet eggs. Results of the study also indicate that with the static system: 1) eggs should be fertilized from each female to retain individual identity; 2) eggs should be dispersed in Petri dishes to avoid clumping; 3) water should be changed at 24 h, but not at 48 h (neurulation) post-fertilization; and 4) embryos that do not optimally develop should be removed the day after neurulation (72 h of post-fertilization period) and water should be exchanged every day subsequent to the 48 h time-point post-fertilization.
Keywords: Animals; Female; Hatching; Egg; ženské pohlaví; Reproduction; Neurulation; Animal Husbandry; Fishes; vodní hospodářství; Incubation; Aquaculture; ryby; ovum; Fish; Male; Embryonic Development; Ovum; zvířata; embryonální vývoj; chov zvířat; mužské pohlaví